2018
DOI: 10.1021/acsomega.8b01708
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Hydroxycarbonylation of 1-Dodecene in Microemulsion Systems: Does Reaction Performance Care about Phase Behavior?

Abstract: Catalysis, particularly metal-catalyzed reactions in microemulsion systems, offers a sustainable approach for organic reactions in water. However, it is still a challenging task because of the complex role of the nonionic surfactant in such a system and the interaction of the phase behavior and reaction performance. To get a profound knowledge of this role and interaction, a systematic study of the palladium-catalyzed hydroxycarbonylation of 1-dodecene in a microemulsion system is reported. The influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Undeniably, the separation of the dissolved catalyst from the products is the biggest challenge for homogeneous catalysis. There are several approaches available for the separation and reuse of the homogeneous catalyst, e.g., a simple biphasic system [8] or so-called switchable solvent systems, like switchable-hydrophilicity solvents (SHS [9,10]), thermomorphic systems (TMS [11,12]), and microemulsion systems (MES [13,14]). The homogeneously catalyzed reductive amination of aldehydes using aqueous media has also been described in the literature [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Undeniably, the separation of the dissolved catalyst from the products is the biggest challenge for homogeneous catalysis. There are several approaches available for the separation and reuse of the homogeneous catalyst, e.g., a simple biphasic system [8] or so-called switchable solvent systems, like switchable-hydrophilicity solvents (SHS [9,10]), thermomorphic systems (TMS [11,12]), and microemulsion systems (MES [13,14]). The homogeneously catalyzed reductive amination of aldehydes using aqueous media has also been described in the literature [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The determined CMC values confirm the assumed surface activity of the examined ionic liquids and so the ionic liquids may behave like a surfactant. As known from the literature, the surfactant concentration is crucial for the phase behavior and so for the local concentrations at the interfacial area 11. The influence of different ionic liquids and their concentrations on the hydrocarboxylation of 1‐dodecene and the subsequent phase separation of the reaction mixture is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…phase behavior and so for the local concentrations at the interfacial area [11]. The influence of different ionic liquids and their concentrations on the hydrocarboxylation of 1-dodecene and the subsequent phase separation of the reaction mixture is shown in Fig.…”
Section: Determination Of Palladium and Phosphorous Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the broad scope of nucleophiles such as alcohols and phenols, , amines, thiols, or even water and selenols, O- and N-nucleophiles have been the most extensively studied for the manufacturing of the corresponding esters and amides that are significantly important in fine chemical and pharmaceutical industries . While several studies have been reported for the utilization of simple amines and alcohols as model substrates, only a few works focused on the investigation of carbonylation reactions in the presence of homobifunctional and even heterobifunctional nucleophiles.…”
Section: Introductionmentioning
confidence: 99%